As redes de telecomunicações no estado do Paraná e o uso corporativo do território: fluidez e regulação - Santos, Letícia Król (2014)
The years following the XX century and early XXI century provided the great apex of capital internationalization, broadening the medley technical network causing the privatization movement of public companies in Latin America. In Brazil, the process was not different. Among some basic services, the telephony system was privatized, expanding the offer of service, changing the use of the territory, allowing the transition of paradigms and increasing the dissemination of the telecommunication network. In Paraná State, the company sold to the corporations was Telecomunicações do Paraná S/A. (Telepar), providing the corporative use of the territory. In this case, the State appropriates the normative actions and the multinationals appropriates the services and techniques being offered. Meanwhile, the optical fibers services are in the State`s hands, through Copel Telecom. However, the State, the agent that should apply rules to the competition between companies and aid in the offer of services and access to the society, became the agent that encourages the capital accumulation and circulation in favor of the corporations. The companies direct the capital and the norm is presented as the privatization itself, while the State accompanies this process, configuring a hybrid regulation of territory.